Rainfall partitioning through a mixed cedar swamp and associated C and N fluxes in Southern Ontario, Canada. Issue 11 (25th March 2019) - Duval, Tim P.
Abstract: Partitioning of rainfall through a forest canopy into throughfall, stemflow, and canopy interception is a critical process in the water cycle, and the contact of precipitation with vegetated surfaces leads to increased delivery of solutes to the forest floor. This study investigates the rainfall partitioning over a growing season through a temperate, riparian, mixed coniferous‐deciduous cedar swamp, an ecosystem not well studied with respect to this process. Seasonal throughfall, stemflow, and interception were 69.2%, 1.5%, and 29.3% of recorded above‐canopy precipitation, respectively. Event throughfall ranged from a low of 31.5 ± 6.8% for a small 0.8‐mm event to a high of 82.9 ± 2.4% for a large 42.7‐mm event. Rain fluxes of at least 8 mm were needed to generate stemflow from all instrumented trees. Most trees had funnelling ratios <1.0, with an exponential decrease in funnelling ratio with increasing tree size. Despite this, stand‐scale funnelling ratios averaged 2.81 ± 1.73, indicating equivalent depth of water delivered across the swamp floor by stemflow was greater than incident precipitation. Throughfall dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) averaged 26.60 ± 2.96 and 2.02 ± 0.16 mg L −1, respectively, which were 11 and three times above‐canopy rain levels. Stemflow DOC averaged 73.33 ± 7.43 mg L −1, 35 times higher than precipitation, and TDN was 4.45 ± 0.56 mg L −1, 7.5 times higher than rain. Stemflow DOC concentration was highest from Populus balsamifera and TDN greatest from Thuja occidentalis trees. Although total below‐canopy flux of TDN increased with increasing event size, DOC flux was greatest for events 20–30 mm, suggesting a canopy storage threshold of DOC was readily diluted. In addition to documenting rainfall partitioning in a novel ecosystem, this study demonstrates the excess carbon and nitrogen delivered to riparian swamps, suggesting the assimilative capacity of these zones may be underestimated.